2019
DOI: 10.1088/1742-6596/1231/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report of Light Pollution in Indonesia Based on Sky Quality Observation

Abstract: We observed night sky quality in several LAPAN stations (Agam, Bandung, Pontianak, Sumedang, Garut, Pasuruan, and Biak) which were conducted from April until July 2018 using Unihedron Sky Quality Meter LU-DL type. Observational data from all of the observational points were then sent regularly to a centralized database for further use. Although most of the measurements were done in overcast conditions, we were able to determine the representative clear sky brightness statistically. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The results showed that there are some variations of light pollution across Indonesia. In this respect most of the stations have moderate pollution as can be seen from the values of Biak, Agam, Sumedang, and Pontianak (20.0, 19.5, 19.6,and 17.7 mpsas respectively). On the other hand, the stations which are located near or in cities have high light pollution (Bandung and Pasuruan with 17.1 and 18.0 mpsas, respectively).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The results showed that there are some variations of light pollution across Indonesia. In this respect most of the stations have moderate pollution as can be seen from the values of Biak, Agam, Sumedang, and Pontianak (20.0, 19.5, 19.6,and 17.7 mpsas respectively). On the other hand, the stations which are located near or in cities have high light pollution (Bandung and Pasuruan with 17.1 and 18.0 mpsas, respectively).…”
mentioning
confidence: 85%
“…The purpose of this article is to present the current understanding of light pollution in Indonesia using observations in several locations in Indonesia. Preliminary reports and analyzes of these works can be seen at Admiranto et al [16,17]. Section 2 describes the equipment, data, and methodology of obtaining the data.…”
Section: Introductionmentioning
confidence: 99%
“…Sky Quality Meter (SQM) is a simple and very easy to use photometric tool for measuring sky brightness levels. SQM is produced by Unihedron, and has been widely used for sky quality mapping research [23], [24] determine astronomical site [25], [26] , light pollution research [25], [27]- [29] research in the health sector [28] , behavioural research birds [30], [31] , to research on determining the time prayer [2], [8], [13], [15] . SQM uses a light frequency sensor TSL237, SQM in this study is set to quantify in mpsas every 1 minute with the direction of the sensor to the zenith [32].…”
Section: Sky Quality Metermentioning
confidence: 99%
“…Light pollution is today acknowledged as a global problem that, similar to other forms of anthropogenic pollution, has significant impacts on ecosystems and wildlife, causing adverse effects on living organisms (Chepesiuk 2009;Bennie et al 2015;Irwin 2018;Manríquez et al 2019;Svechkina et al 2020). Originally discussed by the professional astronomical community, which was concerned that the inefficient, unnecessary, and uncontrolled use of artificial light at night (hereafter ALAN) could dazzle professional observatories by impeding their vision of the starry sky (Walker 1970;Riegel 1973), nowadays ALAN has become a fertile field for interdisciplinary scientific research (e.g., Maggi & Benedetti-Cecchi 2018;Admiranto et al 2019;Jechow 2019;Cavazzani et al 2020Cavazzani et al , 2022Kolláth et al 2020), socio-economic studies (e.g., Nordhaus 1994;Gallaway et al 2010;Pérez Vega et al 2022), and wide-ranging cultural debates (e.g., Drake 2019; Hamacher et al 2020).…”
Section: Introductionmentioning
confidence: 99%